HUBUNGAN ANTARA PENGETAHUAN, SIKAP, PERSEPSI, MOTIVASI, DUKUNGAN KELUARGA DAN SUMBER INFORMASI PASIEN PENYAKIT JANTUNG KORONER DENGAN TINDAKAN PENCEGAHAN SEKUNDER FAKTOR RISIKO (STUDI KASUS DI RSPAD GATOT SOEBROTO JAKARTA) - Indrawati, Lina (Jurnal Ilmiah Widya, 2014)
Prevalence of Coronary Heart Disease (CHD) in Indonesia is still very high and is as the leading cause of death for cardiovascular disease. Prevention efforts are needed both primary and secondary to the control of risk factors for CHD. The objective of this is to analyze the factors related to the patient's ability to perform secondary prevention of CHD. The method used a descriptive cross sectional analytic approach to the amount of CHD respondents 68 people and had undergone coronary angiography. Data were collected using a questionnaire of knowledge, attitude, perception, motivation, family support and resources as well as the ability to perform secondary prevention of risk factors with reference KAP questionnaire. The results shows that of this study are factors that there is a relationship between knowledge of the patient's ability to perform secondary prevention of CHD risk factors include knowledge , attitude, self-perception, motivation and family support as well as the source of information. The results of this study can be used as a reference in the development of peer group programs, health education and discharge planning focused on CHD patients.